VoIP Accessibility: A Usability Study of Voice over Internet Protocol (VoIP) Systems and a Survey of VoIP Users with Vision Loss. (January 2018) - Packer, Jaclyn; Reuschel, William
Introduction: Accessibility of Voice over Internet Protocol (VoIP) systems was tested with a hands-on usability study and an online survey of VoIP users who are visually impaired. The survey examined the importance of common VoIP features, and both methods assessed difficulty in using those features. Methods: The usability test included four paid participants who are blind and four who have low vision. Four different tasks using four different VoIP systems (two Windows-based, two iOS-based) were presented in random order. The online survey included participants with prior VoIP experience: 50 individuals who were blind and 22 who have low vision. Results: Usability test participants found that receiving an incoming call was the easiest task and transferring a call was the most difficult. Those with previous iOS experience had a large advantage with the two iOS systems over those with little experience. For the online survey, most respondents (81%) had used VoIP at home for personal use and 49% had used it in their workplace. The caller ID feature was most important to participants, yet only slightly more than half found the feature easy to use; this feature was the most discrepant between importance and ease of use (p < .01). Call management was the most difficult feature for respondents. Generally, those with low vision found features to be more accessible than did those who are blind. Discussion: Almost, all usability study participants reported that they could use all four systems in a real-world setting. Although some of the features were readily usable, many of the VoIP features that respondents to the online survey considered to be important were difficult for them to use. This finding indicates a serious gap between what is presently offered and what is needed for true accessibility by those with vision loss, indicating the necessity of adding accessible features to all VoIP systems. Implications for practitioners: Rehabilitation staff members and teachers of young adults with vision loss should become familiar with current VoIP systems and introduce them to their clients and students in order to increase their future prospects for employment.